A Study of Aerobic Gram-Positive cocci and Gram-Negative bacilli and their Antibiotic Susceptibility Pattern Associated with Mobile Phones of Healthcare Workers in a Tertiary Care Hospital: - Yadav, Kumari Ragani; Shrestha, Kewal; Yadav, Rajiv; Yadav, Bikram; Singh, Ganesh Kumar; Kumar, Prabhat (Birat Journal of Health Sciences, 2025)
Introduction: Mobile phones are an often-overlooked source of microbial contamination in healthcare settings and pose a serious risk for the spread of hospital-acquired infection. Objectives: The objective of this study was to isolate the aerobic gram-positive cocci and gram-negative bacilli and their antibiotic susceptibility pattern from healthcare workers' mobile phones in a hospital. Methodology: The hospital-based descriptive cross-sectional study was conducted in the Clinical Microbiology Laboratory of Nobel Medical College Teaching Hospital, Biratnagar, Nepal, from May 2024 to October 2024. Identification of pathogenic aerobic gram-positive cocci and gram-negative bacilli from mobile phones of healthcare workers (HCW) was done by standard protocol, and antimicrobial susceptibility testing was done by Kirby- Bauer disc diffusion method following Clinical Laboratory Standard Institute guidelines. Results: A total of 215 (100%) swab samples were collected from healthcare workers' mobile phones, 152 (70.6%) samples showed significant bacterial growth by culture, and 63 (29.3%) mobile phone samples showed no growth. The most common organisms isolated were Staphylococcus aureus, followed by Escherichia coli and coagulase-negative Staphylococcus (CONS). All the gram-positive cocci were sensitive to linezolid, teicoplanin, and vancomycin, and gram-negative aerobic bacteria other than Pseudomonas were sensitive to gentamycin, cephalosporins, and Extended-Spectrum Beta-Lactamase (ESBL) producing gram-negative aerobes were sensitive to meropenem, piperacillin/tazobactam and cefepime. Conclusion: The present study highlights that healthcare workers' mobile phones carry pathogenic organisms, the most common in our setting was Staphylococcus aureus. This study also showed that gram-positive cocci were sensitive to linezolid, teicoplanin, and vancomycin, and gram-negative aerobic bacilli other than Pseudomonas were sensitive to gentamycin, cephalosporins, and ExtendedSpectrum Beta-Lactamase (ESBL) producing gram-negative aerobes were sensitive to meropenem, piperacillin/tazobactam and cefepime.